2018
DOI: 10.1098/rstb.2017.0404
|View full text |Cite
|
Sign up to set email alerts
|

Using museum specimens to track morphological shifts through climate change

Abstract: Museum specimens offer a largely untapped resource for detecting morphological shifts in response to climate change. However, morphological shifts can be obscured by shifts in phenology or distribution or sampling biases. Additionally, interpreting phenotypic shifts requires distinguishing whether they result from plastic or genetic changes. Previous studies using collections have documented consistent historical size changes, but the limited studies of other morphological traits have often failed to support, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 42 publications
0
39
0
1
Order By: Relevance
“…Specimens can similarly capture trait shifts through time. In an empirical example of tracking functionally significant traits on butterfly specimens, MacLean et al [53] measure wing melanism-a trait that controls butterfly body temperature-in montane butterflies from North America across 60 years using museum specimens.…”
Section: Diverse Applications Of Collections Data In Global Change Rementioning
confidence: 99%
“…Specimens can similarly capture trait shifts through time. In an empirical example of tracking functionally significant traits on butterfly specimens, MacLean et al [53] measure wing melanism-a trait that controls butterfly body temperature-in montane butterflies from North America across 60 years using museum specimens.…”
Section: Diverse Applications Of Collections Data In Global Change Rementioning
confidence: 99%
“…There are, however, some potential problems in using museum collections as metadata are often incomplete or missing altogether, which reduces the number of useable specimens (Johnson et al, ; Lister et al, ), and specimens are usually collected opportunistically rather than systematically as part of long‐term projects (Kharouba, Lewthwaite, Guralnick, Kerr, & Vellend, ). Additionally, museum specimens often do not provide an ecological context, such as other species present or abiotic environmental factors, and therefore, the drivers of change may not be apparent (MacLean, Nielsen, Kingsolver, & Buckley, ). When species are well represented in collections, however, they provide a unique opportunity to study changes in species body size over a long time period (decades to centuries; Kharouba et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, museum specimens often do not provide an ecological context, such as other species present or abiotic environmental factors, and therefore, the drivers of change may not be apparent (MacLean, Nielsen, Kingsolver, & Buckley, 2018). When species are well represented in collections, however, they provide a unique opportunity to study changes in species body size over a long time period (decades to centuries; Kharouba et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This evolutionary change only altered the phenotype at certain photoperiods, corresponding to the times of year which experienced the greatest change. Given the broad interest in phenotypic and evolutionary responses to climate change (Gienapp et al 2008; Visser 2008; Huey et al 2012; Schilthuizen& Kellerman 2013; Maclean et al 2018; Kelly 2019), our results indicate that changes found at certain times of year may not occur in others, an important limitation to studies that only look at traits under a limited range of seasonal or other conditions. This result shows the potential for independent evolution of different parts of the reaction norm instead of evidence for constraint by genetic correlation across environments, addressing a classic question about the evolution of plasticity (Via & Lande 1985; de Jong 1995; Via et al .…”
Section: Discussionmentioning
confidence: 83%
“…For example, in many regions mean winter and spring temperatures have increased more than summer temperatures (IPCC 2013), leading to greater phenological changes for species active earlier in the year (Walther et al 2002; Menzel et al 2006; Calinger et al 2013; Ovaskainen et al 2013). Climate change has also led to phenotypic changes for many organisms (MacLean et al 2018), the most common of which is declining body size (Gardner et al 2011). However, photoperiod itself does not change with climate change.…”
Section: Introductionmentioning
confidence: 99%